Systematic review of the risks of carotid endarterectomy in relation to the clinical indication for and timing of surgery. - Bond, R; Rerkasem, K; Rothwell, P (2003)
BACKGROUND AND PURPOSE: Reliable data on the risk of carotid endarterectomy (CEA) in relation to clinical indication and timing of surgery are necessary to target CEA more effectively, to inform patients, to adjust risks for case mix, and to understand the mechanisms of operative stroke. METHODS: We performed a systematic review of all studies published from 1980 to 2000 inclusive that reported the risk of stroke and death resulting from CEA. Pooled estimates of risk by type of presenting ischemic event and time since the last event were obtained by Mantel-Haenszel meta-analysis. RESULTS: Of 383 published studies, only 103 stratified risk by indication. Although the operative risk for symptomatic stenosis overall was higher than for asymptomatic stenosis (odds ratio [OR], 1.62; 95% confidence interval [CI], 1.45 to 1.81; P<0.00001; 59 studies), risk in patients with ocular events only tended to be lower than for asymptomatic stenosis (OR, 0.75, 95% CI, 0.50 to 1.14; 15 studies). Operative risk was the same for stroke and cerebral transient ischemic attack (OR, 1.16; 95% CI, 0.99 to 1.35; P=0.08; 23 studies) but higher for cerebral transient ischemic attack than for ocular events only (OR, 2.31; 95% CI, 1.72 to 3.12; P<0.00001; 19 studies) and for CEA for restenosis than primary surgery (OR, 1.95; 95% CI, 1.21 to 3.16; P=0.018; 6 studies). Urgent CEA for evolving symptoms had a much higher risk (19.2%, 95% CI, 10.7 to 27.8) than CEA for stable symptoms (OR, 3.9; 95% CI, 2.7 to 5.7; P<0.001; 13 studies), but there was no difference between early (<3 to 6 weeks) and late (>3 to 6 weeks) CEA for stroke in stable patients (OR, 1.13; 95% CI, 0.79 to 1.62; P=0.62; 11 studies). All observations were highly consistent across studies. CONCLUSIONS: Risk of stroke and death resulting from CEA is highly dependent on the clinical indication. Audits of risk should be stratified accordingly, and patients should be informed of the risk that relates to their presenting event.